Rolling of Logs in Felling Coupes: a Potential Disease Hazard in Coniferous Forests - Singh, Sujan; Pandey, P. C. (Indian Forester, 1989)
Field investigations conducted in five felling coupes of Rampur and Kotgarh Forest Divisions (Himachal Pradesh) during 1985 and 1986 showed that out of 250 trees assessed, 77.2 per cent were wounded by rolling of billets after felling along hill slopes for their subsequent collection at road side. Fungal decay had established on 49.5 per cent of a total of 367 wounds and was 1 cm and more in depth in 54.6 per cent of infected wounds. Incidence of wounding on trunk and root and butt regions was more or less same. Three types of fungi namely sap rot funei (confined to dead sapwood), trunk-rot fungi and root and butt-rot fungi were detected on the infected wounds. Polyporus schweinitzii and Fomes geotropus were indentified as trunk-rot fungi and Heterobasidion annosum and Armillarielia mellea as root-fot pathogens. Field investigations indicated that out of a total of 367 wounds on 250 assessed trees, 193 wounds would take more than 10 years, out of which 64 will take more than 10 years to get callused over. The risk of their being colonized by trunk and root-rot pathogens would thus remain very high.